Potential Effects of Changes in Temperature and Food Resources on Life History Trajectories of Juvenile Oncorhynchus mykiss. Issue 1 (21st December 2012) - Benjamin, Joseph R.; Connolly, Patrick J.; Romine, Jason G.; Perry, Russell W.
Abstract: Increasing temperatures and changes in food resources owing to climate change may alter the growth and migratory behavior of organisms. This is particularly important for salmonid species like Oncorhynchus mykiss, where some individuals remain in freshwater to mature (nonanadromous Rainbow Trout) and others migrate to sea (anadromous Steelhead). Whether one strategy is adopted over the other may depend on the individual's growth and size. In this study, we explored (1) how water temperature in Beaver Creek, a tributary to the Methow River, Washington, may increase under four climate scenarios, (2) how these thermal changes may alter the life history trajectory followed by O. mykiss (i.e., when and if to smolt), and (3) how changes in food quality or quantity might interact with increasing temperatures. We combined bioenergetic and state‐dependent life history models parameterized for O. mykiss in Beaver Creek to mimic baseline life history trajectories. Based on our simulations, when mean water temperature was increased by 0.6°C there was a reduction in life history diversity and a 57% increase in the number of individuals becoming smolts. When mean temperature was increased by 2.7°C, it resulted in 87% fewer smolts than in the baseline and fewer life history trajectories expressed. A reduction in food resources led to slower growth, more life history trajectories, and a greater proportion of smolts. In contrast, when food resources were increased, fish grew faster, which reduced the proportion of smolts and life history diversity. Our modeling suggests that warmer water temperatures associated with climate change could decrease the life history diversity of O. mykiss in the central portion of their range and thereby reduce resiliency to other disturbances. In addition, changes in food resources could mediate or exacerbate the effect of water temperature on the life history trajectories of O. mykiss .